Physeter macrocephalus ... - Luque, José L.; Muniz-Pereira, Luís C.; Siciliano, Salvatore; Siqueira, Liege R.; Oliveira, Magda S.; Vieira, Fabiano M. (Zenodo, 2010)
Physeter macrocephalus Anisakis physeteris ... : Published as part of Luque, José L., Muniz-Pereira, Luís C., Siciliano, Salvatore, Siqueira, Liege R., Oliveira, Magda S. & Vieira, Fabiano M., 2010, Checklist of helminth parasites of cetaceans from Brazil, pp. 57-68 in Zootaxa 2548 on page 63, DOI: 10.5281/zenodo.196777 ...